Analisis Penokohan Hans Landa Sebagai Tokoh Antagonis Dalam Film Inglourious Basterds - Anastasia, Jesika; Mau, Muliadi; Sonni, Alem Febri; Nugraha, Arya (Universitas Garut, 2024)
Antagonis, Manipulatif, Kompleksitas